2020
DOI: 10.4018/ijsda.2020100106
|View full text |Cite
|
Sign up to set email alerts
|

A Systems Dynamics Approach to Understanding the Determinants of Antenatal Care Utilization in Low-and Middle-Income Countries

Abstract: There has been low adherence of antenatal care utilization (ANC) in low and middle-income countries (LMIC) despite its associated negative outcome on women and their unborn babies. Although several studies have examined ANC, the majority focus on isolated aspects and do not explore the holistic approach to understand its dynamics. The system dynamics approach provides a deeper understanding of the phenomenon by examining the underlying factors, causes, effects, feedback, and delays. This study aimed at underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Yang et al 2020), the effects of housing supply shortage on housing choice (Karlen et al 2022), or homelessness and climate change (Ramin & Svoboda 2009). Beyond involving a larger panel of experts, meta-narrative (Kim et al 2021;Wong et al 2013), scoping or systematic reviews (Namatovu & Semwanga 2020;Singh et al 2021) of non-research stakeholders in the elicitation of variables and interrelationships as well as in the generation of data for spatiotemporal analyses (e.g. community based or participatory system dynamics; Hovmand 2014; Macmillan et al 2016).…”
Section: Moving Forward: Discussion and Conclusionmentioning
confidence: 99%
“…Yang et al 2020), the effects of housing supply shortage on housing choice (Karlen et al 2022), or homelessness and climate change (Ramin & Svoboda 2009). Beyond involving a larger panel of experts, meta-narrative (Kim et al 2021;Wong et al 2013), scoping or systematic reviews (Namatovu & Semwanga 2020;Singh et al 2021) of non-research stakeholders in the elicitation of variables and interrelationships as well as in the generation of data for spatiotemporal analyses (e.g. community based or participatory system dynamics; Hovmand 2014; Macmillan et al 2016).…”
Section: Moving Forward: Discussion and Conclusionmentioning
confidence: 99%
“…Digital literacy among users in the healthcare ecosystem is paramount to changing attitude and shaping perception. This can be achieved through massive sensitization, 98 training end-users, garnering support at the national and hospital levels. There is need to empower women to appreciate their role in the health service delivery not just as service consumers but also as service advisors.…”
Section: Discussionmentioning
confidence: 99%
“…With many perceiving these technologies as not useful, it is not surprising that eHealth adoption still remains in balance. Although some studies have underscored the importance of digital technologies in maternal health, 29,98 some mothers instead felt that these systems are intrusive and would widen the patient-doctor gap, yet many could not envisage service delivery without physical contact with the doctor. The limited knowledge as revealed in other studies, 29,30 impedes the mother's ability to use digital technologies not just as avenues of improved interaction and efficiency but also as platforms for improved access, especially in rural areas.…”
Section: Behavioural Intentionmentioning
confidence: 99%
“…It is established that when employs goals are aligned with company strategic goals, they boost organizational productivity (Elharakany, Moscardini, Khalifa, & Abd Elghany, 2018;Trybou, Gemmel, Desmidt, & Annemans, 2017). In addition to that studies found that employee's enthusiasm and strong motivation towards achieving firm goals significantly contributes towards organizational productise (Dewett, 2007;Galli, 2019;Ha & Lo, 2018;Hirst et al, 2009) (Namatovu & Semwanga, 2020;Trybou et al, 2017). Earlier studies have found a strong linkage between achieving strategic goal of firm and organizational productivity (Ashraf, 2012;Chakraborty & Biswas, 2019;Dewett, 2007;Dobre, 2013;Ha & Lo, 2018;Hirst et al, 2009;Shah, 2011;Trybou et al, 2017); S. Wang and Noe (2010).…”
Section: Achieving Strategic Goal Of Firmmentioning
confidence: 95%